ANALYSIS OF CONFLICT MANAGEMENT STYLE OF CORRECTIONAL DEVELOPMENT DEVELOPMENT - Naniek Pangestuti (Polteknik Ilmu Pemasyarakatan, 2018)
Understanding conflict management is very important, especially in Prison Houses and Correctional Institutions. By understanding the conflict of prisoners, it will be able to overcome the vulnerability of conflicts that often end in riots. This study uses quantitative research methods in the form of surveys to measure the tendency of conflict management to prisoners. The results showed that of the five conflict management styles, the majority of respondents chose dominance management styles, then the rankings below were collaborative, compromise, and lastly avoidance management styles. None of the respondents chose the accommodation conflict management style